Formation mechanism and governance strategies of stigma in public health emergencies: Based on event system theory - Liu, Shuzhen; Liu, Yuanyuan; Guo, Ming; Wang, Rui; Sun, Qiong; Zhu, Rong (Frontiers in Public Health, 2023)
With the new coronavirus (COVID-19) pandemic across the world, it is critical to propose effective strategies for stigma governance in public health emergencies in order to reduce negative effects caused by stigma. However, no known research has focused on the essential role of events in understanding stigma phenomenon from the perspective of external dynamic changes. Based on the event system theory, this paper analyzes the evolution mode and characteristics of specific events in the process of stigmatization from strength, space and time aspects, and taking COVID-19 event as an example, 1202 questionnaires and empirical analysis were conducted. Our results reveal that event strength directly affects the results of stigmatization, and such impact appears to be more prominent with a novel, disruptive and critical event. In addition, spatial and temporal attributes represent the dynamic development of an event, and they can interact with event strength to regulate the relationship between event strength and outcomes. Finally, stigma governance strategies under public health emergencies from three aspects of event strength, space, and time were put forward.